Comparison of tissue damage and inflammation for robotic laparoscopy and conventional laparoscopy in early endometrial cancer - Meng, Shengnan; Cao, Yanling; Shen, Qingwei; Dong, Ling; Wang, Nan (Frontiers in Medicine, 2024)
This study was to analyze the dynamics of tissue damage and inflammatory response markers perioperatively and whether these differ between robotic laparoscopy and conventional laparoscopy in early endometrial cancer. In a randomized controlled trial conducted at SHANGHAI FIRST MATERNITY and INFANT HOSPITAL, eighty women with early-stage, low-risk endometrial cancer were randomly assigned to receive either robotic or conventional laparoscopy. Blood samples were collected at admission, immediately before surgery, 2 hours after surgery, 24 hours after surgery, 48 hours after surgery, and one week after surgery. The samples were analyzed for various biomarkers associated with inflammatory processes and tissue damage. These included high-sensitivity C-reactive protein (hs-CRP), white blood cell count (WBC), platelet count, interleukin-6 (IL-6), cortisol, creatine kinase (CK), and tumor necrosis factoralpha (TNF-α). These markers provide insights into the underlying physiological responses and potential tissue-level changes within the study participants. There was no significant difference in clinical and preoperative data between two groups. The results showed that the patients who underwent robotic laparoscopy had a longer presurgical time compared to the conventional laparoscopy group. However, the robotic group had shorter operating times, quicker vaginal cuff closures, and lower estimated blood loss compared to the conventional laparoscopy group. The hospital stays, Visual Analog Scale (VAS) score and drainage volume on the first day after operation were lower in robotic group compared to conventional laparoscopy group. hs-CRP, WBC, IL-6 and cortisol were significantly lower in the robotic group, though the differences were transient. This study demonstrated that robotic laparoscopy, used in early endometrial cancer treatment, leads to a reduced inflammatory response, less tissue damage, and lower stress levels, as evidenced by decreased levels of hs-CRP, IL-6, and cortisol, compared to conventional laparoscopy. These findings suggest that robotlaparoscopy may facilitate a quicker recovery and improve patient-reported outcomes.